Urban atmospheric dust, i.e. PM2.5 and yellow sand adsorption inhibitor for soft contact lenses
The adsorption of inorganic particles is inhibited by copolymers of specific structures, and the problem of surface adsorption of soft contact lenses is solved, the symptoms of allergic conjunctivitis and the discomfort of wearing are alleviated, and the effective inhibition of inorganic particles is achieved.
Patent Information
- Application Number
- CN202180022607.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-22
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-03-22
AI Technical Summary
The prior art is difficult to effectively inhibit the adsorption of inorganic microparticles (such as PM10, PM5, PM2.5) on the surface of soft contact lenses, resulting in the persistence of allergic conjunctivitis and the physical method fails after the attachment of atmospheric pollutants.
A copolymer with a specific structure, containing 2-(meth)acryloyloxyethylphosphate choline, an alkyl group-containing (meth)acrylic acid-based monomer and a quaternary ammonium group-containing (meth)acrylic acid-based monomer formed by As an inorganic microparticle adsorption inhibitor, the copolymer inhibits the adsorption of inorganic microparticles through the molecular chain structure.
It effectively inhibits the adsorption of inorganic particles, relieves and allergic conjunctivitis symptoms, improves wear discomfort, and maintains the adsorption and adhesion of soft contact lenses.
Smart Images

Figure FDA0005140442390000011 
Figure FDA0005140442390000012 
Figure GDA0005140442400000031
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic fine particle adsorption inhibitor for soft contact lenses containing a copolymer having a specific structure. Background Art
[0002] In the field of ophthalmology, the main cause of allergic conjunctivitis is believed to be pollen particles such as cedar pollen and cypress pollen, indoor dust, etc. However, it has also been reported that due to the influence of global air pollution in recent years, inorganic micro-particles such as yellow sand, PM10 or PM2.5 can also cause allergic conjunctivitis (Non-patent Document 1, Non-patent Document 2). These air pollutants adhere to and adsorb on the conjunctiva, cornea, etc., thereby causing allergic symptoms, such as congestion, eye mucus, and tears. Therefore, various technical developments for treating, alleviating, and preventing these allergic symptoms have been carried out, such as: as a pharmaceutical / chemical method, a method of treating and alleviating using pharmaceuticals and eye drops with antiallergic drugs (Patent Document 1); as a physical method, a method of wearing glasses, masks, etc., to inhibit the contact of air pollutants with the conjunctiva and cornea from the very beginning (Patent Document 2, Patent Document 3), etc. It is known that pharmaceutical / chemical methods have high effectiveness, but they can produce side effects such as inducing drowsiness. In addition, physical methods are effective before atmospheric pollutants attach to and adsorb to the conjunctiva and cornea, but are believed to lose their effectiveness once atmospheric pollutants attach to and adsorb to the conjunctiva and cornea.
[0003] Furthermore, for soft contact lens wearers, once these air pollutants adhere to and adsorb on the surface of the soft contact lenses, they are difficult to rinse off with tears, artificial tears, etc., and there is also a concern that allergic symptoms may persist for a long time.
[0004] Therefore, there is a need to develop technologies that can alleviate allergic symptoms and relieve and reduce discomfort by inhibiting the adhesion and adsorption of atmospheric pollutants to the conjunctiva, cornea, and further to the surface of soft contact lenses. However, the development of these technologies has not been fully carried out, and effective methods are still unknown.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-203791
[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-134100
[0009] Patent Document 3: Japanese Patent Application Publication No. 2014-111147
[0010] Non-patent literature
[0011] Non-patent document 1: Tatsuya Mimura, Title 1. Allergies and environmental factors in the field of ophthalmology, Allergy, 63(7), 901-906, 2014.
[0012] Non-patent document 2: Tatsuya Mimura et al., Airborne particulate matter (PM2.5) and the prevalence of allergic conjunctivitis in Japan, Science of the Total Environment, 493-499, 2014. Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention aims to provide an inorganic fine particle adsorption inhibitor for soft contact lenses, which inhibits the adsorption of inorganic fine particles such as PM10, PM5, and PM2.5 on the surface of soft contact lenses, thereby alleviating and reducing the symptoms of allergic conjunctivitis and further improving the discomfort.
[0015] Methods for solving problems
[0016] In order to solve the above problems, the present inventors conducted intensive research and found that the adsorption of inorganic harmful particles such as PM10, PM5, and PM2.5 can be suppressed by using a material containing a copolymer having a specific weight average molecular weight and a specific structure for soft contact lenses. It was found that it is possible to provide an inorganic particle adsorption inhibitor for soft contact lenses that can alleviate and reduce the symptoms of allergic conjunctivitis and further improve the discomfort, thereby completing the present invention.
[0017] That is, the inorganic fine particle adsorption inhibitor for soft contact lens of the present invention is as follows.
[0018] [1] An inorganic fine particle adsorption inhibitor for soft contact lenses, comprising a copolymer (P) having a weight average molecular weight of 10,000 to 5,000,000, comprising 10 to 90 mol % of a structural unit (A) based on 2-(meth)acryloyloxyethyl phosphorylcholine, and 90 to 10 mol % of at least one structural unit selected from the group consisting of a structural unit (B1) based on an alkyl-containing (meth)acrylic monomer, a structural unit (B2) based on a quaternary ammonium group-containing (meth)acrylic monomer, and a structural unit (B3) based on a (meth)acrylamide monomer.
[0019] [Chemistry 1]
[0020]
[0021] [Chemistry 2]
[0022]
[0023] [Chemistry 3]
[0024]
[0025] [Chemistry 4]
[0026]
[0027] (In formula (A), R 1 represents a hydrogen atom or a methyl group. 2 represents a hydrogen atom or a methyl group, R 3 represents an alkyl group having 4 to 18 carbon atoms. 4 represents a hydrogen atom or a methyl group, R 5 , R 6 and R 7 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, and X - represents a halogen ion or an acid residue. In formula (B3), R 8 represents a hydrogen atom or a methyl group, R 9 and R 10 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. )
[0028] Effects of the Invention
[0029] By using the inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention, the adsorption of inorganic fine particles of PM2.5, PM5, and PM10 after wearing soft contact lenses can be suppressed, and the symptoms of allergic conjunctivitis can be alleviated and reduced, thereby also improving the discomfort. DETAILED DESCRIPTION
[0030] The inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention contains a copolymer (P).
[0031] The present invention will be described below in detail.
[0032] In this specification, when the preferred numerical range (such as the range of concentration, weight-average molecular weight, etc.) is described in sections, each lower limit and upper limit can be independently combined. For example, in the description of "preferably 10 or more, more preferably 20 or more, and preferably 100 or less, more preferably 90 or less", "preferable lower limit: 10" and "preferable upper limit: 90" can be combined to obtain "10 or more and 90 or less". For example, in the description of "preferably 10 to 100, more preferably 20 to 90", "10 to 90" can also be obtained.
[0033] In the present invention, "(meth)acrylic acid" means acrylic acid or methacrylic acid (methacrylic), "(meth)acryloyl" means acryloyl or methacryloyl (methacryl), and "(meth)acrylate" means acrylate or methacrylate (methacrylate).
[0034] <Inorganic fine particle adsorption inhibitor for soft contact lenses>
[0035] The inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention contains a copolymer (P) comprising a structural unit (A) based on 2-(meth)acryloyloxyethyl phosphorylcholine and at least one structural unit selected from the group consisting of a structural unit (B1) based on an alkyl group-containing (meth)acrylic monomer, a structural unit (B2) based on a quaternary ammonium group-containing (meth)acrylic monomer, and a structural unit (B3) based on a (meth)acrylamide monomer.
[0036] <Structural Unit (A) Based on 2-(Meth)acryloyloxyethyl Phosphorylcholine>
[0037] The structural unit (A) based on 2-(meth)acryloyloxyethyl phosphorylcholine is represented by the following formula (A), and more specifically, is obtained by polymerizing a monomer represented by formula (A').
[0038] [Chemistry 5]
[0039]
[0040] [Chemistry 6]
[0041]
[0042] In formula (A) and formula (A'), R 1 It may be a hydrogen atom or a methyl group, and is preferably a methyl group.
[0043] The copolymer (P) used in the present invention can exhibit an effect of suppressing adsorption of inorganic fine particles to soft contact lenses by having the structural unit (A) in the molecular chain.
[0044] The content of the structural unit (A) in the copolymer (P) used in the present invention is 10 to 90 mol%. If the content is less than 10 mol%, the inorganic microparticle adsorption inhibitory effect cannot be expected; if it is more than 90 mol%, the adsorption to soft contact lenses is reduced due to the super hydrophilicity of the (meth)acryloyloxyethyl phosphorylcholine chain segment, and the inorganic microparticle adsorption inhibitory effect cannot be expected to be imparted to the soft contact lenses.
[0045] The content of the structural unit (A) in the copolymer (P) is preferably 20 to 90 mol%, more preferably 30 to 90 mol%.
[0046] <Structural Unit (B1) Based on Alkyl Group-Containing (Meth) Acrylic Monomer>
[0047] The structural unit (B1) based on the alkyl-containing (meth)acrylic monomer is represented by the following formula (B1), and more specifically, is obtained by polymerization of the monomer represented by formula (B1'). The copolymer (P) used in the present invention can enhance the effect of inhibiting the adsorption of inorganic microparticles to soft contact lenses by having the structural unit (B1) in the molecular chain.
[0048] [Chemistry 7]
[0049]
[0050] [Chemistry 8]
[0051]
[0052] In formula (B1) and formula (B1'), R 2 It may be a hydrogen atom or a methyl group, and is preferably a methyl group. 3 The alkyl group has 4 to 18 carbon atoms and may be a linear or branched alkyl group.
[0053] Specifically, examples of the straight-chain alkyl group having 4 to 18 carbon atoms include n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, and n-octadecyl. Examples of the branched-chain alkyl group having 4 to 18 carbon atoms include tert-butyl, isobutyl, isopentyl, tert-pentyl, neopentyl, isohexyl, isoheptyl, isooctyl, isononyl, isodecyl, isoundecyl, isododecyl, isotridecyl, isotetradecyl, isopentadecyl, isohexadecyl, isoheptadecyl, and isooctadecyl.
[0054] From the viewpoint of the effect of the copolymer (P) in suppressing adsorption of inorganic fine particles to soft contact lenses, n-butyl, n-dodecyl and n-octadecyl are preferred.
[0055] As long as the structure satisfies the structural unit (B1), there is no concern that the adsorption of the copolymer to soft contact lenses will be impaired, and therefore any monomer can be used. However, from the viewpoint of achieving a higher adsorption effect of the copolymer to soft contact lenses, preferred examples of the alkyl group-containing (meth)acrylic acid-based monomer include butyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate, among which stearyl (meth)acrylate is more preferred.
[0056] <Structural Unit (B2) Based on Quaternary Ammonium Group-Containing (Meth) Acrylic Monomer>
[0057] The structural unit (B2) based on the (meth) acrylic monomer containing a quaternary ammonium group is represented by the following formula (B2), and more specifically, is obtained by polymerization of the monomer represented by formula (B2'). The copolymer (P) used in the present invention can enhance the effect of inhibiting the adsorption of inorganic microparticles to soft contact lenses by having the structural unit (B2) in the molecular chain.
[0058] [Chemistry 9]
[0059]
[0060] [Chemistry 10]
[0061]
[0062] In formula (B2) and formula (B2'), R 4 It may be a hydrogen atom or a methyl group, and is preferably a methyl group. 5 , R 6 and R 7 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, and the alkyl group may be linear, branched or cyclic.
[0063] Specifically, as R 5 , R 6 and R 7 , examples include methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, n-octyl, isooctyl, cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl.
[0064] As R 5 , R 6 and R 7 , preferably methyl, ethyl, propyl, isopropyl, more preferably methyl.
[0065] As X - Examples of the moiety include halogen ions such as chloride ions, and acid residues such as sulfate ions and methylsulfate ions. Halogen ions are preferred.
[0066] From the viewpoint of enhancing the effect of the copolymer in suppressing adsorption of inorganic fine particles to soft contact lenses, preferred examples of the quaternary ammonium group-containing (meth)acrylic monomer include 2-hydroxy-3-(meth)acryloyloxypropyltrimethylammonium chloride.
[0067] <Structural Unit (B3) Based on (Meth) Acrylamide Monomer>
[0068] The structural unit (B3) based on the (meth)acrylamide monomer is represented by the following formula (B3), and more specifically, is obtained by polymerization of the monomer represented by formula (B3'). The copolymer (P) used in the present invention has the structural unit (B3) in the molecular chain, which can increase the molecular weight of the copolymer and make the copolymer more effective in inhibiting the adsorption of inorganic particles to soft contact lenses.
[0069] [Chemistry 11]
[0070]
[0071] [Chemistry 12]
[0072]
[0073] In formula (B3) and formula (B3'), R 8 It may be a hydrogen atom or a methyl group, and is preferably a hydrogen atom. 9 and R 10 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be any of a linear, branched, or cyclic group. Specifically, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, isohexyl, cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl groups may be mentioned. 9 and R 10 , preferably a hydrogen atom, a methyl group, an ethyl group, a propyl group or an isopropyl group, and more preferably a methyl group.
[0074] From the viewpoint of increasing the molecular weight of the copolymer and enhancing the effect of suppressing adsorption of inorganic fine particles to the soft contact lens, preferred examples of the (meth)acrylamide monomer include N,N-dimethylacrylamide and the like.
[0075] The copolymer (P) used in the present invention has at least one structural unit selected from the group consisting of (B1), (B2) and (B3) in its molecular chain. The copolymer used in the present invention may have only any one structural unit selected from the group consisting of (B1), (B2) and (B3) in its molecular chain, may have two structural units selected from the group consisting of (B1), (B2) and (B3) (e.g., a combination of (B1) and (B2), a combination of (B2) and (B3), a combination of (B3) and (B1)), or may have all the structural units of (B1), (B2) and (B3).
[0076] Since the copolymer (P) used in the present invention has not only the structural units (B1) to (B3) but also the structural unit (A) in the same polymer chain, the copolymer (P) used in the present invention becomes an inorganic fine particle adsorption inhibitor for soft contact lenses that exhibits an inorganic fine particle adsorption inhibitory effect on soft contact lenses.
[0077] The content of the structural units (B1) to (B3) in the copolymer (P) used in the present invention (when only one of the structural units (B1) to (B3) is contained, the content of the structural unit; when two or three of the structural units (B1) to (B3) are contained, the content of the structural units is the total) is 10 to 90 mol%, preferably 10 to 80 mol%, and more preferably 10 to 70 mol%. If the content is less than 10 mol%, the hydrophilicity of the copolymer increases, the adsorption or adhesion to the soft contact lens is poor, and there is a concern that the effect of inhibiting the adsorption of inorganic fine particles cannot be expected; if the content is more than 90 mol%, the solubility in water decreases, and there is a concern that it is difficult to prepare an inorganic fine particle adsorption inhibitor for soft contact lenses.
[0078] From the viewpoint of exhibiting the effect of inhibiting adsorption of inorganic fine particles to soft contact lenses, preferred examples of the combination of the structural unit (A) and the structural units (B1) to (B3) contained in the molecular chain of the copolymer (P) used in the present invention include the following combinations.
[0079] 2-(Meth)acryloyloxyethyl phosphorylcholine and butyl (meth)acrylate,
[0080] 2-(Meth)acryloyloxyethyl phosphorylcholine and stearyl (meth)acrylate,
[0081] 2-(Meth)acryloyloxyethylphosphorylcholine and 2-hydroxy-3-(meth)acryloyloxypropyltrimethylammonium chloride, and
[0082] 2-(Meth)acryloyloxyethyl phosphorylcholine, N,N-dimethylacrylamide and stearyl (meth)acrylate.
[0083] The copolymer used in the present invention may contain structural units other than the structural unit (A) and the structural units (B1) to (B3), but is preferably composed of the structural unit (A) and one, two or three structural units selected from the group consisting of the structural units (B1), (B2) and (B3). Among them, the combination of (A) and (B1), the combination of (A) and (B2), and the combination of (A), (B1) and (B3) are preferred, among which the combination of (A) and (B1), the combination of (A), (B1) and (B3) are more preferred, and the combination of (A) and (B1) is even more preferred.
[0084] The weight average molecular weight of the copolymer used in the present invention is 10,000 to 5,000,000, preferably 20,000 to 2,000,000. If the weight average molecular weight is less than 10,000, the adsorption or adhesion to soft contact lenses is reduced, and the inorganic fine particle adsorption inhibitor effect cannot be expected; if the weight average molecular weight is greater than 5,000,000, the viscosity increases sharply, and there is a concern that it is difficult to prepare an inorganic fine particle adsorption inhibitor for soft contact lenses.
[0085] The weight average molecular weight of the copolymer (P) is determined by GPC (gel permeation chromatography) measurement in terms of polyethylene glycol.
[0086] The copolymer (P) of the present invention may use a single copolymer with a specific weight average molecular weight, or may use a mixture of two or more copolymers with different weight average molecular weights. By using a mixture of two or more copolymers with different weight average molecular weights, the effect of suppressing the adsorption of inorganic fine particles to soft contact lenses by these copolymers (P) is improved.
[0087] When two kinds are used in combination, a combination of a copolymer (P1) having a weight average molecular weight of 200,000 to 800,000 and a copolymer (P2) having a weight average molecular weight of 900,000 to 1,500,000, or a combination of a copolymer (P1′) having a weight average molecular weight of 250,000 to 800,000 and a copolymer (P3) having a weight average molecular weight of 10,000 to 200,000 is preferred.
[0088] The blending ratio of the copolymer (P1) to the copolymer (P2) is 1:9 to 9:1, preferably 3:7 to 7:3, and more preferably 4:6 to 6:4, by weight.
[0089] The blending ratio of the copolymer (P1′) to the copolymer (P3) is 1:9 to 9:1, preferably 3:7 to 7:3, and more preferably 4:6 to 6:4, by weight.
[0090] The inorganic particle adsorption inhibitor for soft contact lenses of the present invention preferably contains 0.001 to 5.0 w / v% of the copolymer (P) and water as a solvent. In addition, as a solvent, a mixed solvent of water and alcohol can be used. Examples of the alcohol include methanol, ethanol, n-propanol, isopropanol, and the like. In this case, the inorganic particle adsorption inhibitor for soft contact lenses of the present invention can be obtained by dissolving the copolymer (P) in water or the above-mentioned mixed solvent in an amount of 0.001 to 5.0 w / v%. If the concentration of the copolymer (P) is less than 0.001 w / v%, a sufficient inorganic particle adsorption inhibitory effect cannot be obtained; if the concentration of the copolymer (P) exceeds 5.0 w / v%, there is a concern that an inorganic particle adsorption inhibitory effect that matches the compounding amount cannot be obtained.
[0091] The concentration of the copolymer (P) is preferably 0.01 to 5.0 w / v%, more preferably 0.01 to 4.0 w / v%, further preferably 0.01 to 3.0 w / v%.
[0092] The water used in the present invention can be any water as long as it is used for the production of pharmaceuticals or has an equivalent quality thereto. For example, water described in the Japanese Pharmacopoeia can be used.
[0093] By using the copolymer (P) of the present invention in soft contact lenses, the adsorption of inorganic fine particles during wearing of soft contact lenses can be suppressed, allergic conjunctivitis can be alleviated and reduced, and the effect of improving the discomfort during wearing of soft contact lenses can be imparted.
[0094] The inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention can exhibit an adsorption inhibitory effect on inorganic fine particles (PM10 [particles having a particle size of about 10 μm or less and passing through a particle classification device with a collection efficiency of 50% at a particle size of 10 μm, etc.].
[0095] Specifically, it is effective for tiny particulate matter that is an inorganic particle (PM10 [particles with a particle size of approximately 10 μm or less and that pass through a particle classifier with a capture efficiency of 50% at a particle size of 10 μm], PM5 [particles with a particle size of approximately 5 μm or less and that pass through a particle classifier with a capture efficiency of 50% at a particle size of 5 μm], PM2.5 [particle size of approximately 2.5 μm or less and that pass through a particle classifier with a capture efficiency of 50% at a particle size of 2.5 μm]), yellow sand, and falling smoke.
[0096] The inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention may be formulated, in addition to the copolymer (P) and water, with decongestant ingredients, anti-inflammatory / astringent ingredients, vitamins, amino acids, sulfonamides, sugars, cooling agents, inorganic salts, salts of organic acids, acids, bases, antioxidants, stabilizers, preservatives, mucin secretagogues, etc., which are generally used in ophthalmic preparations, as required.
[0097] Examples of the decongestant component include epinephrine or a salt thereof, ephedrine hydrochloride, tetrahydrozoline hydrochloride, naphazoline or a salt thereof, phenylephrine, and methylephedrine hydrochloride.
[0098] Examples of the anti-inflammatory / astringent component include ε-aminocaproic acid, allantoin, berberine or a salt thereof, sodium azulenesulfonate, glycyrrhizic acid or a salt thereof, zinc lactate, zinc sulfate, and lysozyme chloride.
[0099] Examples of the vitamins include sodium flavin adenine dinucleotide, cyanocobalamin, retinyl acetate, retinyl palmitate, pyridoxine hydrochloride, panthenol, sodium pantothenate, and calcium pantothenate.
[0100] Examples of the amino acids include aspartic acid or a salt thereof and aminoethanesulfonic acid.
[0101] Examples of the sulfonamide drug include sulfamethoxazole or a salt thereof, sulfadiazine, and sulfadiazine sodium.
[0102] Examples of the sugars include glucose, mannitol, sorbitol, xylitol, and trehalose.
[0103] Examples of the cooling agent include menthol and camphor.
[0104] Examples of the inorganic salt include sodium chloride, potassium chloride, borax, sodium hydrogen carbonate, sodium hydrogen phosphate, and anhydrous sodium dihydrogen phosphate.
[0105] Examples of the salt of an organic acid include sodium citrate.
[0106] Examples of the acid include boric acid, phosphoric acid, citric acid, sulfuric acid, acetic acid, and hydrochloric acid.
[0107] Examples of the base include sodium hydroxide, potassium hydroxide, trishydroxymethylaminomethane and monoethanolamine.
[0108] Examples of the antioxidant include tocopherol acetate and dibutylhydroxytoluene.
[0109] Examples of the stabilizer include sodium edetate and glycine.
[0110] Examples of the preservative include benzalkonium chloride, chlorhexidine gluconate, potassium sorbate, methyl parahydroxybenzoate, ethyl parahydroxybenzoate, propyl parahydroxybenzoate, isopropyl parahydroxybenzoate, butyl parahydroxybenzoate, isobutyl parahydroxybenzoate, and polyhexamethylene biguanide hydrochloride.
[0111] Examples of the mucin secretagogue include diquafosol sodium and rebamipide.
[0112] The specific product form containing the inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention is not particularly limited as long as it is an ophthalmic preparation, and the following preparations can be listed. For example, soft contact lens care products such as eye drops, contact lens wearing solutions, contact lens cleaning solutions, contact lens cleaning and storage solutions, and contact lens filling solutions can be listed.
[0113] From the viewpoint of improving its inorganic microparticle adsorption inhibitory effect, the inorganic microparticle adsorption inhibitor for soft contact lenses of the present invention is preferably used for soft contact lenses of Group III and Group IV in the FDA classification (ionic soft contact lenses). It should be noted that the FDA classification is a classification of soft contact lenses stipulated by the U.S. Food and Drug Administration (FDA), and stipulates that Group I is a soft contact lens with a water content of less than 50% and non-ionic, Group II is a soft contact lens with a water content of 50% or more and non-ionic, Group III is a soft contact lens with a water content of less than 50% and ionic, and Group IV is a soft contact lens with a water content of 50% or more and ionic.
[0114] Specific examples of soft contact lenses classified as Group III or Group IV include the following products. (The values in parentheses indicate the water content, and the following values indicate the main components constituting the soft contact lenses.)
[0115] (Group III soft contact lenses)
[0116] balafilcon A (36%, Tris-VC, NVP)
[0117] (Group IV soft contact lenses)
[0118] Etafilcon A (58%, 2-hydroxyethyl methacrylate / methacrylic acid), ocufilcon B (52%, 2-hydroxyethyl methacrylate / methacrylic acid), ocufilcon D (55%, 2-hydroxyethyl methacrylate / methacrylic acid), phemefilcon A (55%, 2-hydroxyethyl methacrylate / ethoxyethyl methacrylate / methacrylic acid), vifilcon A (55%, 2-hydroxyethyl methacrylate / polyvinyl pyrrolidone / methacrylic acid), methafilcon A (55%, 2-hydroxyethyl methacrylate / methacrylic acid), bufilcon A (55%, 2-hydroxyethyl methacrylate / diacetone acrylamide / methacrylic acid), perfilcon A (71%, 2-hydroxyethyl methacrylate / N-vinyl pyrrolidone / methacrylic acid), SEED 1daypure moisture plus (58%, 2-hydroxyethyl methacrylate / quaternary ammonium group-containing methacrylate compound / carboxyl group-containing methacrylate compound / methacrylic acid / ethylene glycol dimethacrylate)
[0119] Among them, from the viewpoint of suppressing the adsorption of inorganic fine particles to the soft contact lens, a soft contact lens of Group IV is preferred, and a soft contact lens of Group IV having a water content of 55% or more is more preferred.
[0120] Example
[0121] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples on the inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention, but the present invention is not limited thereto. The copolymers used in the present Examples and Comparative Examples are as follows.
[0122] Copolymer (P1): 2-methacryloyloxyethyl phosphorylcholine / butyl methacrylate copolymer [structural unit (A) 80 mol%, structural unit (B1) 20 mol%, weight average molecular weight: 600,000].
[0123] Copolymer (P2): 2-methacryloyloxyethyl phosphorylcholine / butyl methacrylate copolymer [structural unit (A) 80 mol%, structural unit (B1) 20 mol%, weight average molecular weight: 1,100,000].
[0124] Copolymer (P3): 2-methacryloyloxyethyl phosphorylcholine / butyl methacrylate copolymer [structural unit (A) 80 mol%, structural unit (B1) 20 mol%, weight average molecular weight: 150,000].
[0125] Copolymer (P4): 2-methacryloyloxyethyl phosphorylcholine / butyl methacrylate copolymer [structural unit (A) 30 mol%, structural unit (B1) 70 mol%, weight average molecular weight: 142,000].
[0126] Copolymer (P5): 2-methacryloyloxyethyl phosphorylcholine / stearyl methacrylate copolymer [structural unit (A) 80 mol%, structural unit (B1) 20 mol%, weight average molecular weight: 60,000].
[0127] Copolymer (P6): 2-methacryloyloxyethyl phosphorylcholine / 2-hydroxy-3-methacryloyloxypropyltrimethylammonium copolymer [structural unit (A) 70 mol%, structural unit (B2) 30 mol%, weight average molecular weight: 450,000].
[0128] Copolymer (P7): 2-methacryloyloxyethyl phosphorylcholine / N,N-dimethylacrylamide / stearyl methacrylate copolymer [structural unit (A) 50 mol%, structural unit (B3) 45 mol%, structural unit (B1) 5 mol%, weight average molecular weight: 200,000].
[0129] Polymer for Comparative Example (Q1): A polymer of butyl methacrylate [weight average molecular weight: 180,000] purchased from Fujifilm Wako Pure Chemical Industries, Ltd. (product name: poly(n-butyl methacrylate)) was used.
[0130] Comparative Example Polymer (Q2): A polymer of 2-hydroxy-3-methacryloyloxypropyltrimethylammonium (weight average molecular weight: 300,000), obtained by polymerization according to the method described in Example 8-258403 of Japanese Patent Application Laid-Open No. 2001-08-258403.
[0131] Comparative Example Polymer (Q3): A polymer of N,N-dimethylacrylamide [number average molecular weight: 10,000] purchased from Sigma-Aldrich Japan (product name: Poly (N,N-dimethylacrylamido), DDMAT terminated) was used for the test.
[0132] The weight average molecular weight of each of the above copolymers was measured by GPC (gel filtration chromatography). The measurement conditions of GPC are as follows.
[0133] GPC system: High performance liquid chromatography system CCP&8020 series (manufactured by Tosoh Corporation)
[0134] Chromatographic column: Shodex OHpak SB-802.5HQ (manufactured by Showa Denko K.K.) and SB-806HQ (manufactured by Showa Denko K.K.) connected in series
[0135] Developing solvent: 20 mM sodium phosphate buffer (pH 7.4)
[0136] Detector: Differential refractive index detector, UV detector (wavelength 210nm)
[0137] Molecular weight standard: EasiVial PEG / PEO (manufactured by Agilent Technologies)
[0138] Flow rate: 0.5mL / min
[0139] Column temperature: 45°C
[0140] Sample: The obtained copolymer was diluted with a developing solvent to a final concentration of 0.1 wt %
[0141] <Phosphate Buffer>
[0142] Phosphate buffer (hereinafter referred to as "PBS") was used in the inorganic microparticle adsorption test. PBS (composition: 0.02 w / v% potassium chloride, 0.02 w / v% potassium dihydrogen phosphate, 0.8 w / v% sodium chloride, 0.115 w / v% disodium hydrogen phosphate) manufactured by Sigma-Aldrich was used.
[0143] <Inorganic fine particle adsorption test>
[0144] The adsorption test of inorganic fine particles to soft contact lenses was carried out according to the following procedure.
[0145] (1) One soft contact lens was taken out of the blister package and washed with PBS. The washed soft contact lens was placed in a 24-well plate, and 2 mL of the solution of each example or each comparative example was added.
[0146] (2) Then, shake for 1 hour.
[0147] (3) Using urban air dust (PM2.5, manufactured by the National Institute for Environmental Studies), PBS, and an ultrasonic homogenizer (homogenizer treatment: 1 minute), an urban air dust concentration of 1 mg / mL was prepared (hereinafter referred to as an "air dust solution").
[0148] (4) A new 24-well plate was prepared, 1.5 mL of the atmospheric dust solution was added thereto, and the soft contact lens prepared in (2) was further immersed for 1 hour.
[0149] (5) After immersion, the soft contact lens was taken out and washed three times with 10 mL of PBS.
[0150] (6) After washing, the transmittance of the soft contact lens was measured, and the amount of atmospheric dust adsorbed on the surface of the soft contact lens (the amount of inorganic fine particles adsorbed) was measured.
[0151] In addition, regarding the inorganic fine particle adsorption test, the inorganic fine particle adsorption inhibitory effect was judged according to the following criteria.
[0152] The inorganic fine particle adsorption inhibition rate was calculated using the following formula based on Comparative Examples 1-4 and 3-1 to 3-2 to determine the presence or absence of the inorganic fine particle adsorption inhibition effect.
[0153] (Inorganic fine particle adsorption inhibition rate) = {1-((Inorganic fine particle adsorption amount of each Example or each Comparative Example) / (Inorganic fine particle adsorption amount of each Comparative Example using the corresponding soft contact lens / particle type))}×100
[0154] (Judgment Criteria)
[0155] The inorganic particle adsorption inhibition rate is more than 70%: The inorganic particle adsorption inhibition effect is extremely excellent
[0156] The inorganic microparticle adsorption inhibition rate is 50% or more and less than 70%: The inorganic microparticle adsorption inhibition effect is excellent
[0157] Inorganic particle adsorption inhibition rate is 30% or more and less than 50%: Inorganic particle adsorption inhibition effect is achieved
[0158] Inorganic particle adsorption inhibition rate is less than 30%: No inorganic particle adsorption inhibition effect
[0159] [Example 1-1]
[0160] About 80 g of purified water was weighed, and 1.0 g of copolymer (P1) was weighed and added thereto, and stirred. Then, purified water was added to make the total amount 100 mL. Further sterile filtration was performed to obtain a solution of Example 1-1. Its properties are shown in Table 1.
[0161] [Example 1-2 to Example 1-9, Comparative Example 1-1 to Comparative Example 1-4]
[0162] According to the components and amounts described in Table 1, solutions of Examples 1-2 to 1-9 and Comparative Examples 1-1 to 1-4 were prepared in the same manner as in Example 1-1.
[0163] [Example 2-1]
[0164] The above-mentioned inorganic fine particle adsorptivity test was carried out using the solution of Example 1-1 and SEED 1daypure moisture plus (soft contact lens manufactured by SEED).
[0165] [Example 2-2 to Example 2-9, Comparative Example 2-1 to Comparative Example 2-4]
[0166] The inorganic microparticle adsorption test was performed using the solutions and soft contact lenses of the examples or comparative examples shown in Table 2. The inorganic microparticle adsorption test was performed in the same manner as in Example 2-1. Table 2 shows the results of the inorganic microparticle adsorption test of Examples 2-2 to 2-9 and Comparative Examples 2-1 to 2-4.
[0167] [Example 3-1]
[0168] The inorganic fine particle adsorptivity test was conducted in the same manner as in Example 2-1, except that the solution of Example 1-5 was used and the soft contact lens was changed to Bausch & Lomb medalist fresh fit (Bausch & Lomb Japan soft contact lens).
[0169] [Example 3-2 to Example 3-6, Comparative Example 3-1 to Comparative Example 3-2]
[0170] The inorganic microparticle adsorption test was performed using the solutions, soft contact lenses, and microparticle types of the examples described in Table 3. The inorganic microparticle adsorption test was performed in the same manner as in Example 3-1. The results of the inorganic microparticle adsorption test of Examples 3-2 to 3-6 and Comparative Examples 3-1 to 3-2 are shown in Table 3.
[0171] [Table 1]
[0172] Table 1
[0173]
[0174] Water: Japanese Pharmacopoeia purified water, manufactured by Jianrong Pharmaceutical
[0175] *: Insoluble, so cannot be prepared
[0176] [Table 2]
[0177] Table 2
[0178]
[0179] Lens (1): SEED 1daypure moisture plus: manufactured by SEED, power: -3.00D, base curve: 8.8, diameter: 14.2, water content: 58%, monomer composition: 2-HEMA-quaternary ammonium group-containing methacrylate-carboxyl group-containing methacrylate-MAA-EGDMA, FDA classification: Group IV (ionic soft contact lens)
[0180] According to the results of Examples 2-1 to 2-9 and Comparative Examples 2-1 to 2-4, it can be seen that the adsorption of inorganic particles (urban air dust) to soft contact lenses is suppressed by the addition of copolymer (P). In addition, the inorganic particle adsorption suppression effect is improved depending on the concentration of the copolymer (P). Furthermore, according to the results of Examples 2-4 to 2-9, it can be seen that even if the type and combination of the copolymer (P) are changed, the inorganic particle adsorption suppression effect is also shown.
[0181] [Table 3]
[0182] Table 3
[0183]
[0184] Lenses (2): Bausch & Lomb medalist fresh fit: Made in Japan, power: -3.00D, base curve: 8.6, diameter: 14.0, water content: 36%, monomer composition: TrisVC / NVP, FDA classification: Group III (ionic soft contact lenses)
[0185] Yellow sand: Gobi yellow sand (produced by the National Institute for Environmental Studies) was used.
[0186] According to the results of Examples 3-1 to 3-6, it can be seen that the inorganic fine particle adsorption inhibitory effect brought by the copolymer (P) is effective not only for urban air dust, but also for other air pollutants such as yellow sand.
[0187] Industrial Availability
[0188] By using the inorganic fine particle adsorption inhibitor for soft contact lenses of the present invention, it is possible to produce a soft contact lens care product that can inhibit the adsorption of inorganic fine particles to contact lenses, alleviate or mitigate the symptoms of allergic conjunctivitis, and improve discomfort.
Claims
1. An urban atmospheric dust, i.e. PM2.5 and yellow sand adsorption inhibitor for soft contact lenses, comprising a copolymer P having a weight average molecular weight of 10,000 to 5,000,000, comprising 10 to 90 mol % of a structural unit (A) based on 2-(meth)acryloyloxyethyl phosphorylcholine, and 90 to 10 mol % of a structural unit (B1) based on an alkyl-containing (meth)acrylic acid monomer, [Chemistry 1] [Chemistry 2] In formula (A), R 1 represents a hydrogen atom or a methyl group; in formula (B1), R 2 represents a hydrogen atom or a methyl group, R 3 represents an alkyl group having 4 to 18 carbon atoms, The copolymer P comprises a combination of a copolymer P1 having a weight average molecular weight of 200,000 to 800,000 and a copolymer P2 having a weight average molecular weight of 900,000 to 1,500,000, or a combination of a copolymer P1' having a weight average molecular weight of 250,000 to 800,000 and a copolymer P3 having a weight average molecular weight of 10,000 to 200,000. The definitions of copolymer P1, copolymer P2, copolymer P1' and copolymer P3 are the same as those of copolymer P. The mixing ratio of copolymer P1 to copolymer P2 is 3:7 to 7:3 by weight, and the mixing ratio of copolymer P1' to copolymer P3 is 3:7 to 7:3 by weight.
Citation Information
Patent Citations
Transparent film for recording
JP1996258403A
Mask
JP2014111147A
Spectacles with air delivery function
JP2017134100A
Ophthalmologic allergy prophylactic
JP2018203791A
Formulation for oculist
JP1999335301A